Semantic Analysis Of Poetry “Fear No More The Heat O’ The Sun” By William Shakespeare - Said, Ratna; Oktariyani, Oktariyani; Usman, Rahmi; Djafar, Rahmi (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Classical poetry is still very popular today. But in this classic piece of literature, especially in William Shakespeare's poem